The Improvement of Student Learning Outcomes Through Think Pair Share Learning and Assignment Method on Vector Material - Hanifah, Ayu Ismi; Masruroh, Masruroh; Nawafilah, Nur Qomariyah (Department of Mathematics Education , University of Jember, 2022)
Interesting learning is extremely needed to motivate student participation in class. Besides increasing student participation, the existence of different learning than usual is expected to increase students understanding so that student learning outcomes also can increase. In this research, Think Pair Share learning was implemented by combining the assignment method. The objective of this research was to improve student learning outcomes through Think Pair Share learning with the assignment method on vector material. This research was a classroom action research. The data sources of this research came from the answer result of the assignment given, the result of student activity observation, and the result of student response questionnaires. This research used a qualitative descriptive analysis technique. This technique was used to describe the description of activities according to the data obtained. This research concludes that Think Pair Share learning with the assignment method is effective to be implemented in the classroom, as proven by the percentage increase from 65% to 77.5%. Students' responses also indicated a good category, which was 87.8%. The results of this research pointed out that there was an increase in student learning outcomes from cycle I to cycle II, which was from 64.5% to 81.2%.